The Estimation of Mangroves Area and Density of Mangroves Changes Use the Remote Sensing Data at Northheast Province of Aceh, Indonesia - Febriandi, Febriandi (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The aim of the research to mapping mangrove estimate mangroves area in time series data at the years 2000, 2005, 2011, and 2015, and looking for density of mangroves changing at the Northeast Province of Aceh. The methodology use data Landsat TM5, OLI TIRS, Administration map, and tools use by ENVI 4.5, ArcGIS 10.1, technical analysis to interpretation mangroves area used the algorithm the maximum likelihood classification, Kernel density to calculate density of mangroves changing. Result of the research. From the estimation of mangrove land with intrepetasi satellite imagery obtained by maximum likelihood algorithma cotton area of mangroves in the study are always varied and changing, change-oriented land areas surrounding existing land use is not mangrove in mangrove areas. Mangrove areas relative change in Kernel density indicated in the model to observe the point of incidence of the changes experienced more change in the frequency changes in the form of multi-time repeated changes of the time period, and changes in the relatively small area that is always on changing every time calculations.